PEDAGANG KAKI LIMA (PKL) SEBAGAI BIBIT ENTREPRENEUR DALAM MENGATASI PENGANGGURAN - Bagyo Handoko (Jurnal Ilmiah Econosains, 2010)
ABSTRACTStreet Trader in general is consisted of one and or some labours. This thing at the same time can lessen unemployment to remember its absorbent labour. Having beginning of business that is simple in fact they are entrepreneurs seeds that is later can implement its more business kondusif. Legal capital owned is relative smallness, and divided to fixed capital, in the form of equipments, and circulating capital. Very rare fund fulfilled from opening finance companies; usually gets fund or loan from institute or individual of who without ceremony, or stems from supplier which supplayer its merchandise. The low of basic yield street trader and way of management of very simple mony; so possibility to perform very small capital investment and also business expansion. In general this street trader labour included in category which majority stays in main job activity age (prime-age). In enableness street trader, each government city has different policy one another.Keywords: Cloister Trader, Entrepreneur, Unemployment.